Ideal Potentials in Action: Schutzian Affinities in Simmel’s View of Life - Lafontaine, Simon (Simmel Studies)

(untitled) (Edizioni ETS, 2021)
The View of Life is still under-studied despite its status as capstone to Simmel’s work. Departing from Simmel’s image as an unsystematic flâneur or bricoleur, I assess the affinity of his late theory of life forms with Schutz’s analysis of human action in three steps: First, as a common concern with the clarification of foundational problems that coincide with interpretive sociology’s basic idea of tracing back all cultural objectivations to the dynamics of living processes. Second, as an articulation of life’s self-transcendence concordant with the tension between action as a projected act (modo futuri exacti) and as an ongoing process (modo presenti) uncovered by Schutz for the first time in his posthumously published book Life Forms and Meaning Structures. I follow with a third proposal about how Simmel’s line of thought on freedom as a capacity to break through purposiveness and as a rise of ideal constructs might complement Schutz’s attention to the growth of the acting self through life events, suggesting that The View of Life can be regarded as a precedent to Schutz for linking action projection to the development of aspirations and ideals, and to theorize how the realization of projects supports the development of individual integrity and the ability to appropriate one’s life in the midst of unfamiliar and critical situations. Simmel and Schutz are thus shown to contribute to an approach to creative action in sociology.